Phenanthroline-Based Molecular Switches for Prospective Chemical Grafting: A Synthetic Strategy and Its Application to Spin-Crossover Complexes - Mörtel, Max; Lindner, Thomas; Scheurer, Andreas; Heinemann, Frank Wilhelm; Khusniyarov, Marat (Inorganic Chemistry, 2020)
1,10-Phenanthroline represents a well-known versatile ligand system finding many applications in chemistry, biology, and material science. The properties and thus the use of these molecules are determined by coordinating metal ions and ligand substituents. Advanced ligand systems that, for instance, feature simultaneously an integrated photochrome and a surface anchoring group require the introduction of several differing substituents and the synthesis of asymmetric derivatives. In spite of a long history of the ligand system-and to our great surprise-a general synthetic approach allowing the introduction of differing substituents at positions (3,8) and (5,6) of 1,10-phenanthroline is not known. Here, we present a general approach for the synthesis of such phenanthrolines. The approach is used to integrate a diarylethene photochrome into a functionalized phenanthroline and thus to synthesize a novel photoswitchable phenanthroline and a corresponding spin-crossover molecular photoswitch. The functionality of both the ligand and its iron(II) complex at room temperature has been demonstrated. The importance of this work for chemical grafting of molecular switches based on phenanthrolines is emphasized.
CRIS-Team Scopus Importer:2020-03-17